Rationale of Pancheshwar Multipurpose Project for Reduction of Energy Crisis and Mitigating the Impacts of Mahakali Flood and Subsequent Economic Development of Nepal and India (Hydro Nepal: Journal of Water, Energy and Environment, 2014)
The proposed 315m high dam Pancheshwar Multipurpose Project (PMP) is a bi-national scheme on the Mahakali River that forms the border between Nepal and India. In the first week of July 2013, flooding on the Mahakali River caused extensive damages in district headquarter of Darchula district of Nepal and downstream area. The implementation of the proposed Pancheshwar Multipurpose Project (6480+240 MW) could solve the current energy crisis, provide flood control, and generate reliable source of revenue from the export of hydropower for both Nepal and India. However, despite the possible advantages, PMP is still only a plan 18 years after its initiation with the 1996 Mahakali Treaty ratified by the Nepalese parliament. Therefothere, Pancheshwar Multipurpose Project should be jointly developed as soon as possible for the mutual benefit of both nations.DOI: http://dx.doi.org/10.3126/hn.v14i0.11247HYDRO Nepal JournalJournal of Water Energy and EnvironmentVolume: 14, 2014, JanuaryPage: 16-20